Desain Tahapan Pembelajaran Green Chemistry pada Topik Cairan Ionik sebagai Pengawet Bambu untuk Menguatkan Sustainability Literacy melalui Integrasi Kimia, Teknologi dan Rekayasa dalam Pendidikan Calon Guru Kimia - Anita Damayanti, - (2022)
This study aims to produce a design for green chemistry learning stages on the topic of ionic liquids as bamboo preservatives to strengthen sustainability literacy skills through the integration of chemistry, technology and engineering in the education of prospective chemistry teachers. The method used in this study is a mixed method using the Model of Educational Reconstruction (MER) framework. There are three things that need to be considered in the MER research design: (1) Clarification and analysis of science content/scientist conceptions, (2) research on students' pre-conceptions on certain science content, (3) learning design and evaluation. The participants in this study were students of chemistry teacher candidates at one of the public universities in Banten. The instruments used in this research are the format of chemical content analysis related to aspects of green chemistry and sustainability on the topic of ionic liquids through content análisis, interview guidelines, developed learning stage design design, validation sheet for learning stage design, sustainability literacy ability test, understanding test. the conception of prospective chemistry teacher students on the type of ionic liquid as a bamboo preservative, and a questionnaire for the responses of prospective chemistry teacher students on the design of green chemistry-based learning stages. Based on the results of the research that has been done, ionic liquids can be said to be a sustainable material because it is environmentally friendly, In addition, the sustainability literacy profile of students after learning is an average of 72.45%, and the understanding of prospective chemistry teacher students on the topic of ionic liquid as a bamboo preservative is 61.71%. From the research results, the design of the green chemistry learning stages that have been designed can be used in the learning process that can strengthen the sustainability of student literacy.